Influência do espaçamento e densidade de semeadura na produtividade de grãos na cultura da soja - Almeida, Juliano Villanie (2023)
Soybean farming has wide relevance, being among the main national commodities. The objective of this study was to evaluate the grain yield characteristics and main components in modern soybean cultivars recommended for the State of Mato Grosso under different row spacings, and to propose a system of adequacy in the seeder to minimize the time spent with the adjustments in the machines. The trials were carried out in the 2020/2021 harvest in the experimental area of Fazenda Pirapó in the municipality of Ipiranga do Norte in the state of Mato Grosso. The evaluated soybean cultivars were: FOCO 74I77 IPRO, APORÉ 75HO111 IPRO, DM 81I84 IPRO, NEO 750 IPRO, RK 7518 IPRO and NK 7201 IPRO. Two experiments were carried out, in the first experiment the effect of row spacing on productivity components was evaluated, with six soybean cultivars and four row spacing (0.35; 0.40; 0.50 and 0.55 m). In the second experiment, the effect of reducing the number of recommended seeds in different spacing between rows was evaluated (50% reduction in 0.35 m; 40% spacing of 0.40 m; 30% in 0.50 m and 20% at 0.55 m; and the recommended population at 0.50 m. The experimental design used was randomized blocks in strip scheme, with four replications, in a factorial arrangement. The morphophysiological characteristics evaluated were: plant height, diameter of stem, number of stems per plant, height of insertion of the first pod, number of pods per plant, number of grains per pod, number of grains per plant, weight of 1000 grains and grain yield calculated in kg ha-1. data were submitted to analysis of variance, mean comparison test and Pearson's correlation analysis. After the statistical analyzes it was verified that the reduction of the spacing between soybean rows did not contribute to the increase of the productivity of the evaluated cultivars. In the spacing 0.5 0 and 0.55 m it was verified that there was a significant difference, for cultivar NEO 750, being superior in relation to the other cultivars. The reduction of the soybean seed population and the change in spacing did not show a significant difference in relation to productivity.